On the Mathematical Modeling of a Fire Thermogasodynamic Pattern and Using a Priory Calculation of Fire Hazard Factors in Forensic Fire Examination - I. S. Taubkin (Теория и практика судебной экспертизы)
The article presents the disadvantages of the “risk analysis” methodology for fire safety assessment of buildings and its inadmissibility in forensic practice. The option of numerical modeling application for fire hazards evaluation in forensic fire-examination is analyzed.